The epidemiology of Chagas disease in the Americas (2024)
Chagas disease is a complex parasitic zoonosis that still threatens public health across the Americas. Initiatives to control Trypanosoma cruzi transmission via blood transfusion and non-native triatomine-bug vectors have yielded crucial advances